Philosophical interpretations of the image of women as performative act of gendered body and as bodily orientation in space:: M. Merleau-Ponty - J. Buttler - S. Ahmed - Deleuze - Mitrou, Yiannis; Kolyri, Chloé Tzia (Dia-noesis: A Journal of Philosophy, 2025)
This article deals with the issue of the image of women through the body and physicality in general in a dia-phenomenological sense. That is, through M. Merleau-Ponty's phenomenology, J. Butler's phenomeno-logical approach to the relation between the "construction" of gender and the performative act, S. Ahmed's Queer Phenomenology and the orientation of queer things or moments in space and finally Deleuze's topology of the body. The woman as an image will be linked to the image of the body which is both an object and a subject of the action which concerns its position in relation to gender. The body exists in space together with its sexuality which emerges from its performative action of body not only as biological being but as also sexual being throw performative act.